2013
DOI: 10.1039/c3ce40824h
|View full text |Cite
|
Sign up to set email alerts
|

3D porous gear-like copper oxide and their high electrochemical performance as supercapacitors

Abstract: A facile and mild approach was used for the controlled synthesis of 3D porous gear-like CuO on a Cu substrate (PGC) based on annealing gear-like Cu(OH) 2 (GC) at 200 uC in air. There are 3-10 edges that build up a gear-like structure and a huge number of holes formed on each edge. As an integrated nanostructure, the binder-free PGC can be used as a supercapacitors electrode (SC) directly. Due to its 3D porous structure and the highly conductive Cu substrate as a current collector, the integrated electrode exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 44 publications
(43 reference statements)
2
37
1
Order By: Relevance
“…Introducing another metal or metal oxide is also a favorite route [20][21][22][23][24][25][26][27]. Based on these processes, CuO-based pseudocapacitor has enhanced specific capacitance and high rate capability [9,11,14,17,26]. Apart from capacitance, the other preliminary requirement for a high quality pseudocapacitor material is its cyclic stability, especial long-term cyclability.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Introducing another metal or metal oxide is also a favorite route [20][21][22][23][24][25][26][27]. Based on these processes, CuO-based pseudocapacitor has enhanced specific capacitance and high rate capability [9,11,14,17,26]. Apart from capacitance, the other preliminary requirement for a high quality pseudocapacitor material is its cyclic stability, especial long-term cyclability.…”
Section: Introductionmentioning
confidence: 97%
“…Integrating CuO with carbon materials, including porous carbon [3], carbon nanotube [4][5], and graphene [6][7], has proved to be an efficient method. Controlling the shape, morphology, and structure of CuO is also a good solution [1][2][8][9][10][11][12][13][14][15][16][17][18][19]. Introducing another metal or metal oxide is also a favorite route [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Copper oxide films also exhibit modest specific capacitances that may vary between 6 Fg -1 to 43 Fg -1 [8,9]. However, specific capacitance as high as 348 F g -1 has been reported that Cu oxides with 3D porous structures [10]. High surface area/ porosity are therefore key features to optimize the specific capacitance of these materials.…”
Section: Introductionmentioning
confidence: 98%
“…The enhanced electrochemical response of Cu-Fe foams deposited at 1.5 Acm -2 for 90 s can be related to their chemical composition and morphology. When compared to samples deposited for 180 s, they present a higher Fe content(Figure 4) which favour a higher capacitance due to the generally higher capacitance of Fe oxides when compared to copper oxides[5][6][7][8][9][10]. Furthermore, Cu-Fe foams deposited at 90 s also have a lower deposited mass that results in a less developed network morphology than foams deposited at 180 s (…”
mentioning
confidence: 97%
“…The nucleation process on the surface of substrate is quite slow, which avoids the mixed and disorderly arrangement. The hydrothermal method has many advantages: i) this route is very versatile because the hydrothermal process occurs on a variety of materials, such as Ni(OH) 2 [46], MnO 2 [47], Co(OH) 2 [22,48], FeOOH [49], Cu(OH) 2 [50], ZnO [51], V 2 O 5 [52]; ii) the reaction parameters can be easily controlled including temperature, time and concentration, which would result in different morphologies, porosity and compositions of the final products [19,53] [58]), which offer an even higher porosity and mass-loading of the active layer.…”
Section: Substrates and Synthetic Methodsmentioning
confidence: 99%